PEMBERDAYAAN SISWA BERKEBUTUHAN KHUSUS MELALUI PROGRAM MAKRAME (MENGIKAT TALI) (Studi Di Sekolah Luar Biasa Kusuma Bangsa Kelurahan Anggoeya Kecamatan Poasia) - Pradisa, Surya; Yusuf, Bakri; Tawulo, Megawati Asrul (Universitas Halu Oleo, 2023)
This research aims to determine the empowerment of Students with Special Needs in this macrame program activity. This type of research uses qualitative data methods. Determining the informants in this research used the Purposive Sampling method so that the informants were the Principal of the Kusuma Bangsa Special School, the homeroom teacher for Students with Special Needs, and Students with Special Needs. The data sources used in this research are Primary and Secondary Data. The data collection techniques used are interview, observation and documentation methods. The research results show that 1) The Empowerment Process for the Makrame Skills Program for Students with Special Needs at the Kusuma Bangsa Special School has three processes, namely the awareness process, the capacity building process, and the empowerment process. 2) Supporting factors and inhibiting factors in the Empowerment of the Makrame Skills Program for Students with Special Needs at the Kusuma Bangsa Special School. The supporting factors are motivation and government policy. The inhibiting factors are the budget, facilities and infrastructure of Special Schools, and lack of motivation to learn.